The springboard diving techniques analysis - Wang, Q. (International Journal of Sports Science and Engineering, 2008)
The springboard diving techniques are involved the special characteristics of the springboard and the sport biomechanics of human movements. A good diving performance is depends on a good take-off, as to get a good take-off, it involves the diver`s actions on the springboard. In considering the techniques for springboard divers, in the article, I will discuss the springboard special characteristics; the suitable actions for divers to co-operate with the board as the springboard goes down and up; where does the energy come from for the take-off; When the diver takes off as the springboard returns, at what point is the springboard at its highest speed; What are the factors influencing the time of the springboard going down and up..when the board returns, is the extension action useful or not; how can the divers choose the fulcrum; what kind of factors influence the divers loss of energy; Also I will discuss some other factors that are included in the springboard diving techniques, and give some advices for improving the techniques and training.